2018
DOI: 10.3389/fnins.2018.00509
|View full text |Cite
|
Sign up to set email alerts
|

The Study of Visual-Auditory Interactions on Lower Limb Motor Imagery

Abstract: In order to improve the activation of the mirror neuron system and the ability of the visual-cued motor imagery further, the multi-stimuli-cued unilateral lower limb motor imagery is studied in this paper. The visual-auditory evoked pathway is proposed and the sensory process is studied. To analyze the visual-auditory interactions, the kinesthetic motor imagery with the visual-auditory stimulus, visual stimulus and no stimulus are involved. The motor-related rhythm suppression is applied on quantitative evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 60 publications
(63 reference statements)
0
5
0
Order By: Relevance
“…The fact that all control participants showed increases in functional connections at resting-state might suggest that their visual and auditory processing were altered following the MI practice sessions. modulation by the mirror neuron system during MI and visual-occipital stimulation (Yu et al 2018). This relationship might have been elicited during the MI practice of the control subjects, which produced the functional connectivity pattern changes observed in figures 7(A) and 8(A).…”
Section: Fmri Graphsmentioning
confidence: 82%
“…The fact that all control participants showed increases in functional connections at resting-state might suggest that their visual and auditory processing were altered following the MI practice sessions. modulation by the mirror neuron system during MI and visual-occipital stimulation (Yu et al 2018). This relationship might have been elicited during the MI practice of the control subjects, which produced the functional connectivity pattern changes observed in figures 7(A) and 8(A).…”
Section: Fmri Graphsmentioning
confidence: 82%
“…A natural way of interaction is acceptable to users, which increases its usefulness in practice ( Xu et al, 2021 ). Previous studies used visual induction consistent with motor tasks to enhance LMI ability ( Boord et al, 2010 , Kitahara et al, 2017 , Yu et al, 2018 ). Additionally, kinesthetic illusion (KI) is a type of proprioception that can complement the biological control loop.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, it may be more conducive to the training and rehabilitation of most stroke patients. Previous studies have found that activated areas of the cerebral cortex are biased toward the contralateral sensorimotor cortex during performing the LMI and visual observation task ( Li et al, 2015 ; Yu et al, 2018 ). In this research ( Tariq et al, 2020 ), LDA, SVM, and KNN model were used to classify bilateral foot LMI task.…”
Section: Discussionmentioning
confidence: 99%
“…In summary, the study shows that the pitch, volume, and vocal track alternation scheme in a joint audio-visual interaction is closely related to spatial height, distance, and direction in realistic environments. They also have a wide range of applications in the positioning, medical, and transportation fields [38][39][40]. However, there is still a gap in how to efficiently optimize spatial-visual interactions through auditory assistance in MR environments.…”
Section: Introductionmentioning
confidence: 99%